International Business Studies and the Imperative of Context: Exploring the 'Black Whole' in Institutional Theory - Michael Jakobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2014)
The aim of this article is to take a critical look at how to perceive informal institutions within institutional theory. Douglas North in his early works on institutional theory divided the national institutional framework into two main categories, formal and informal institution or constraints as he called them. The formal constraints consisted of political rules, judicial decisions and economic contracts, whereas informal constraints consisted of socially sanctioned norms of behaviour, which are embedded in culture and value systems. As formal constraints are straight forward to deal with the informal ones are much more vaguely defined and thus more difficult to grasp analytical. This imprecise perception of informal constraints is surprising as they basically constitute the foundation of the society in question, whereas formal constraints 'only' constitute the functional aspects of the state apparatus in that particular society. In order to, however, begin excavating what lies further behind the informal constraints and their impact on the functionality of the formal constraints it is important to take an overall critical look at the way in which institutional theory relate to a given societal context. This article suggest that this is done by first employing an overall international business (IB) approach to analyse a national economy, in this case the Malaysian economy. This will not, however, be done according to the generally accepted procedure in IB studies using either a firm specific or a generic market-based approach, but rather by employing a combination of selected IB theories and a 'glocalised reading' on how the relationship between the global economy and a national economy pan out and how this translate into impacting a given societal setup. In other words, IB theories are not only employed in the economic sphere, but also confronted with a variety of societal factors that have a positive or negative impact on the explanatory power of the individual IB theories employed.
hdl:10398/8869
Keywords: 330; Global economy; 'Glocalisation'; International business studies; Institutional theory; Informal constraints; Societal embedment; Malaysia; Internationale Betriebswirtschaftslehre; Globalisierung; Institutionenökonomik; Informelle Wirtschaft; Theorie; Malaysia